Drug Intake Among Teenagers in Nigerian Primary and Secondary Schools: A Challenge to School Social Workers - ABONYI, Sunday Evaritus; ABDULHAMEED, Abdussalam; ARINDE-SIMEON, Titilayo Olamide; ONWUKA, Chukwujekwu Charles (Ilorin Journal of Education, 2023)
The study examined drug intake among teenagers in primary and secondary schools in Nigeria and the challenges posed to school social worker in the process of handling this ugly trend using Ilorin metropolis as a case in point. The study relied purely on primary data (quantitative and qualitative) collected from pupils/students, teachers and other staff attached to both public and privately owned primary and secondary schools in Ilorin metropolis. Findings of the study revealed that the major drugs commonly abused by teenagers include tramadol, methamphetamine, marijuana/cigarette, codeine and others. It was also revealed from the study findings that peer pressure, bad parenting, economic challenges/hardship, unconducive school environment amongst other were the major precipitating factors. The study revealed that the application of social work interventional approaches/techniques and skills (counselling, advocacy, teaching, mediation, coordination and others) have been highly relevant in stemming down the wave of this social malice meddling with the future of Nigerian youths. The study recommended the need for every primary and secondary schools to have social workers and a clinical centre established in each school.